Theoretical Foundations of the Studies of Economic Knowledge - Greg Yudin* (Journal of Economic Sociology, 2011)
One of the most substantial trends in recent social research of the economy is represented by a conceptual change: emphasis gradually shifts from «economic action», «practices» and «institutions» towards «economic knowledge». This does by no means entail that economic behavior should be purged away from social studies of economy, but rather calls for taking into account the close interrelation between knowledge and agency. The importance of the analysis of economic knowledge as a key to understanding both institutional dynamics and purposive action has been repeatedly stressed by two inﬂ uential ﬁ gures in the social studies of the economy — Karl Polanyi and Michel Foucault, but unfortunately disregarded by the majority of their successors. This papers aims at exploring theories of economic knowledge suggested by two great thinkers, but also at synthesizing some crucial theoretical insights attained in the heterogeneous yet consolidating ﬁ eld of the studies of economic knowledge. The main challenge to be tackled is applying the theory of economic knowledge to explaining the shifting boundary of the economic.